Effect of evidence-based nursing practices training programme on the competency of nurses caring for mechanically ventilated patients: a randomised controlled trial - Sameh Elhabashy; Michiko Moriyama; Eman Ibrahim El-Desoki Mahmoud; Basem Eysa (BMC, 2024)
Abstract Background Evidence-Based Practice (EBP) has been recognised worldwide as a standardised approach for enhancing the quality of healthcare and patient outcomes. Nurses play a significant role in integrating EBP, especially in Intensive Care Unit (ICU). Consequently, this study aims to examine the effect of an adapted evidence-based nursing practices training programme on the competency level of nurses caring for mechanically ventilated patients. Methods A prospective open-label parallel 1:1 randomised controlled trial was conducted on 80 nurses caring for ICU patients at the National Hepatology and Tropical Medicine Research Institute, Egypt. The trial was carried out between November 2022 and February 2023 under the registration number NCT05721664. The enrolled nurses were randomly divided into intervention and control groups. The intervention group received the evidence-based nursing practice training programme (EBNPTP) in accordance with the Johns Hopkins EBP conceptional model, whereas the control group received traditional in-service education. Four assessments (one pre- and three post-assessments) were conducted to evaluate nurses' competency level over time using the adapted evidence-based nursing competency assessment checklist. The primary endpoint was an increase the competency levels among nurses caring for mechanically ventilated patients. Results The current study results revealed statistically significant differences between intervention and control groups in relation to their level of competency across the three post-assessments, with (p <.001). The study also demonstrated that the nurses' competency level continued to decline significantly over time, with (p <.001). Additionally, a significant correlation was found between the nurses' pre-assessment and educational level, acting as independent variables (predictors), and the third endpoint assessment (p <.01), indicated by multiple linear regression. Conclusion The EBP training programme demonstrated a significant increase in the nurses' level of competency compared with traditional in-service education. This suggests that by training the nurses in various settings with the essential skills and knowledge for EBP, their competency level can be enhanced, leading to the delivery of effective care and improving patient outcomes. However, the long-term sustainability of the EBP adoptions was insufficient; further studies are needed to investigate the factors that affect the durability of EBP adoption. Trial registration The study was registered with Clinical Trials.gov (Registration # NCT05721664) on 10/02/2023.